A positive cooperativity binding model between Ly49 natural killer cell receptors and the viral immunoevasin m157: kinetic and thermodynamic studies - Romasanta, Pablo Nicolas (2014)
Natural killer (NK) cells discriminate between healthy and virally infected or transformed cells using diverse surface receptors that are both activating and inhibitory. Among them, the homodimeric Ly49 NK receptors, which can adopt two distinct conformations (backfolded and extended), are of particular importance for detecting cells infected with mouse cytomegalovirus (CMV) via recognition of the viral immunoevasin m157. The interaction of m157 with activating (Ly49H) and inhibitory (Ly49I) receptors governs the spread of mouseCMV.Wecarried out kinetic and thermodynamic experiments to elucidate the Ly49/m157 binding mechanism. Combining surface plasmon resonance, fluorescence anisotropy, and circular dichroism (CD), we determined that the best model to describe both the Ly49H/m157 and Ly49I/m157 interactions is a conformational selection mechanism where only the extended conformation of Ly49 (Ly49*) is able to bind the first m157 ligand followed by binding of the Ly49*/m157 complex to the second m157. The interaction is characterized by strong positive cooperativity such that the second m157 binds the Ly49 homodimer with a 1000-fold higher sequential constant than the first m157 (108 versus 105 M-1). Using far-UV CD, we obtained evidence for a conformational change in Ly49 upon binding m157 that could explain the positive cooperativity. The rate-limiting step of the overall mechanism is a conformational transition in Ly49 from its backfolded to extended form. The global thermodynamic parameters from the initial state (backfolded Ly49 and m157) to the final state (Ly49*/(m157)2) are characterized by an unfavorable enthalpy that is compensated by a favorable entropy, making the interaction spontaneous.